Class-based OSPF traffic engineering inspired on evolutionary computation - Sousa, Pedro (2007)
This paper proposes a novel traffic engineering framework able to automatically provide near-optimal OSPF routing configurations for QoS constrained scenarios. Within this purpose, this work defines a mathematical model able to measure the QoS compliance in a class-based networking domain. Based on such model, the NP-hard optimization problem of OSPF weight setting is faced resorting to Evolutionary Algorithms. The presented results show that, independently of other QoS aware mechanisms that might be in place, the proposed framework is able to improve the QoS level of a given domain only taking into account the direct influence of the routing component of the network. The devised optimization tool is able to optimize OSPF weight configurations in scenarios either considering a single level of link weights or using multiple levels of weights (one for each class) in multi-topology routing scenarios.